Structure of acid deoxyribonuclease. Issue 10 (29th March 2017) - Varela-Ramirez, Armando; Abendroth, Jan; Mejia, Adrian A.; Phan, Isabelle Q.; Lorimer, Donald D.; Edwards, Thomas E.; Aguilera, Renato J.
Abstract: Deoxyribonuclease II (DNase II) is also known as acid deoxyribonuclease because it has optimal activity at the low pH environment of lysosomes where it is typically found in higher eukaryotes. Interestingly, DNase II has also been identified in a few genera of bacteria and is believed to have arisen via horizontal transfer. Here, we demonstrate that recombinant Burkholderia thailandensis DNase II is highly active at low pH in the absence of divalent metal ions, similar to eukaryotic DNase II. The crystal structure of B. thailandensis DNase II shows a dimeric quaternary structure which appears capable of binding double-stranded DNA. Each monomer of B. thailandensis DNase II exhibits a similar overall fold as phospholipase D (PLD), phosphatidylserine synthase (PSS) and tyrosyl-DNA phosphodiesterase (TDP), and conserved catalytic residues imply a similar mechanism. The structural and biochemical data presented here provide insights into the atomic structure and catalytic mechanism of DNase II.